Comparing the Quality of Life among Patients with Relapsing Remitting Multiple Sclerosis in Iraq Using Different Disease Modifying Therapies - Yahya, Ruaa Natiq; A.Kasim, Ali; A. Al Gawwam, Gheyath (Iraqi Journal of Pharmaceutical Sciences, 2018)
Multiple sclerosis (MS) is a chronic, inflammatory, immune mediated disease of the central nervous system, mostly affecting young adults with mean age of 30 years, twice as high in women compared to men. The etiology of MS is not fully elucidated. MS symptoms are directly related to demyelination and axonal loss, along with other psychological symptoms, can result in functional limitations, disability and reduced quality of life (QoL). The QoL assessments in patients with a chronic disease may contribute to improving treatment and could even be of prognostic value. The goals of this study were to compare the QoL of Iraqi patients with relapsing remitting multiple sclerosis (RRMS),using three different diseases modifying therapies(DMTs) administered orally, subcutaneously, and by slow infusion; namely, fingolimod,interferonB-1b, and natalizumab, respectively. And to assess the role of disability status, educational status, occupational status, MS duration, and treatment duration as a predictor for the QoL. Functional Assessment of Multiple Sclerosis (FAMS) questionnaire version 4 was used to assess QoL. Sociodemographic and clinical characteristics were tested by univariate and multivariate regression analyses to assess the contribution of these predictors to QoL. No significant differences were found in symptoms, thinking/fatigue subscales and FAMS total scores among the three DMTs. In conclusion: Iraqi MS patients using InterferonB-1b, fingolimod or natalizumab have a comparable low level of QoL. The expanded disability status scale (EDSS) is negatively associated with QoL of MS patients in all of the three therapies, while other predictors such as occupational status, educational status, smoking habit and MS duration have different impact in different treatments.